2017
DOI: 10.3390/nu9060560
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Dose Non-Caloric Sweetener Consumption on Gut Microbiota in Mice

Abstract: Non-caloric artificial sweeteners (NASs) provide sweet tastes to food without adding calories or glucose. NASs can be used as alternative sweeteners for controlling blood glucose levels and weight gain. Although the consumption of NASs has increased over the past decade in Japan and other countries, whether these sweeteners affect the composition of the gut microbiome is unclear. In the present study, we examined the effects of sucralose or acesulfame-K ingestion (at most the maximum acceptable daily intake (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 40 publications
5
77
2
4
Order By: Relevance
“…Our results run counter to those of previous studies that offered saccharin at doses far beyond the acceptable human daily intake (ADI) to the animals (Anderson and Kirkland, 1980;Suez et al, 2014). Similar results have been found for other NNS: acesulfame potassium and aspartame, given at 2.5 times or 30 times the ADI, respectively, promoted alterations in the gut microbiota (Suez et al, 2014;Bian et al, 2017a), whereas no such alterations were found when the ADI was respected (Palmnäs et al, 2014;Uebanso et al, 2017). One exception is the gut dysbiosis and liver inflammatory markers seen in mice receiving water supplemented with saccharin at an ADI-equivalent dose (0.3 mg/mL) (Bian et al, 2017b).…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Our results run counter to those of previous studies that offered saccharin at doses far beyond the acceptable human daily intake (ADI) to the animals (Anderson and Kirkland, 1980;Suez et al, 2014). Similar results have been found for other NNS: acesulfame potassium and aspartame, given at 2.5 times or 30 times the ADI, respectively, promoted alterations in the gut microbiota (Suez et al, 2014;Bian et al, 2017a), whereas no such alterations were found when the ADI was respected (Palmnäs et al, 2014;Uebanso et al, 2017). One exception is the gut dysbiosis and liver inflammatory markers seen in mice receiving water supplemented with saccharin at an ADI-equivalent dose (0.3 mg/mL) (Bian et al, 2017b).…”
Section: Discussioncontrasting
confidence: 98%
“…This class of molecules was first considered inert, but chronic consumption has raised concerns regarding user health and environmental safety (Pepino, 2015;Praveena et al, 2018). Experimental studies suggest that NNS are not as inert as initially thought; dopaminergic degeneration (Amin et al, 2018), changes in the gut microbiota (Suez et al, 2014;Bian et al, 2017a;Uebanso et al, 2017), and cell barrier disruption in vitro (Santos et al, 2018) have been described as consequences of their chronic intake.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was reported that mice with 1.5 and 15 mg kg −1 sucralose administration for 8 weeks did not show significant weight gain compared with mice not exposed to sucralose . There are some hypotheses that might explain the contradiction: (i) researches on same sweetener with different concentrations; (ii) sweetener with the same concentration provide different sweetness for animals or humans.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some epidemiological studies involving these sweeteners have generally shown neutral to mildly beneficial metabolic outcomes with the use of artificial sweeteners, such as weight stabilization or less weight regained after dieting . Uebanso et al reported in their study that mice with added 1.5 and 15 mg kg −1 sucralose for 8 weeks did not show significant weight gain compared with mice not exposed to sucralose …”
Section: Introductionmentioning
confidence: 95%
“…Rodents, rats and mice mainly, are frequently used as model organisms for basic research on metabolism. Metabolic profiling was performed on rodent muscle , heart , liver , brain , intestinal and glioma tissue, arterial cells as well as on rodent serum/plasma , urine and feces . CE‐MS was furthermore used for research on the metabolism of microorganism , plants and mushroom .…”
Section: Analytical Applicationsmentioning
confidence: 99%